Sectoral Approach to the Drivers of Productivity Growth in Poland A Firm-Level Perspective on Technology Adoption and Firm Capabilities (Other Economic and Sector Work Reports, 2022)
The report presents the main structural characteristics of the sectors included in the Technology Adoption Survey (TAS) implemented in Poland and provides sectoral TAS results for general and sector-specific business functions, comparing Poland to a peer country, Korea. Nine sectors analyzed within TAS include agriculture, food processing, wearing apparel, motor vehicles, pharmaceuticals, basic metals, wholesale and retail trade, financial services, and land transport. These form a selection of the most important economic industries in agriculture, manufacturing, and services. The same sectors were chosen in all countries where TAS was implemented because of their important contributions to the national economies as well as their diversity, which allowed us to identify the different natures of their technological needs and the barriers to technology adoption. Sectors in Poland differ in technology sophistication in both general business and sector-specific functions but, to a large extent, those differences are driven by the sectors' structural differences, such as the number of large firms, the share of exporters, and the number foreign-owned enterprises. Firms in different sectors face different economic conditions and are exposed to a different balance of regulatory, environmental, and geopolitical risks and challenges. Understanding those sectoral differences, especially as they affect the use of sector-specific technologies, is of utmost importance, because productivity improvements historically have been driven primarily by capital-intensive investment, which often involves sector-specific technologies. In the context of sector-specific technologies, it is worth noting that the level of sophistication differs between sectors. Comparing technology trends across sectors is beyond the scope of this report, however; rather, here we closely follow the methodology described in Bridging the Technological Divide: Technology Adoption by Firms in Developing Countries